Endoscopic retrograde cholangiopancreatography for the treatment of common bile duct dilatation with choledocholithiasis in children: a single-center retrospective cohort study of 58 cases - Xin Wang; Hua Liu; Wenhai Li; Hu Yang; Jun Yang; Hongqiang Bian; Xufei Duan; Hongxi Guo (BMC Pediatrics)
Abstract Background Congenital biliary dilatation (CBD) represents a prevalent congenital anomaly in pediatric surgery, with concurrent choledocholithiasis observed in a notable subset of pediatric patients. Improper management of such cases can compromise early diagnosis of CBD and adversely impact outcomes of radical surgery. This retrospective study evaluated the safety and efficacy of endoscopic retrograde cholangiopancreatography (ERCP) in pediatric patients with common bile duct dilatation complicated by choledocholithiasis, aiming to refine clinical strategies for diagnosis and preoperative management to mitigate long-term complications. Methods A retrospective analysis was conducted on pediatric patients diagnosed with common bile duct dilatation and stones who underwent therapeutic ERCP at Wuhan Children’s Hospital from August 2019 to July 2024. Clinical data, including demographic characteristics, laboratory tests, imaging findings, and ERCP-related parameters, were reviewed. Further subgroup analyses were performed based on the presence of postoperative adverse events and the coexistence of pancreaticobiliary maljunction (PBM). Results A total of 58 children with common bile duct dilatation and stones underwent 58 ERCP procedures, achieving a 100% procedural success rate. After ERCP, liver transaminase and bilirubin levels significantly decreased (P < 0.01). Postoperative follow-up showed a choledochal diameter of < 10 mm in 43 patients, with an overall effectiveness rate of 74.1% (n = 43/58). Among patients who did not undergo radical surgery (n = 48), the prognosis during follow-up (mean duration: 29.9 months) was favorable, and Likert scores were not associated with the presence of PBM (P > 0.05). The incidence of postoperative adverse events (n = 11/58, 19.0%) was significantly correlated with cannulation duration (P < 0.01). Patients in the PBM group (n = 21/58, 36.2%) were more likely to be female, younger, and have lower height and weight, with no differences found in other characteristics. Conclusion ERCP is a safe and effective treatment for pediatric common bile duct dilatation with stones. Regardless of whether radical surgery was performed or the presence of PBM, patients showed improved laboratory parameters and symptom relief following ERCP. The effectiveness and incidence of adverse events were not related to PBM, but postoperative adverse events were associated with cannulation duration. Beyond its diagnostic utility in CBD and PBM, ERCP serves as a safe bridging therapy prior to radical surgery.